290 Effects of Exogenous Follicle Stimulating Hormone Prior to Embryo Transfer on Beef cow Recipients. (21st September 2022) - Larson, Jamie E; Carter, Bryan; Johnson, Tate; Swanson, Rebecca M; Messman, Riley D; Lemley, Caleb O
Abstract: Objectives were to evaluate characteristics of corpora lutea (CL) and concentrations of progesterone (P4) in beef recipient cows stimulated with follicle stimulating hormone (FSH) prior to embryo transfer. Forty suckled beef cows received the CO-Synch+CIDR protocol and were randomly assigned to one of two treatments: 1) exogenous FSH (FSH; 1.0 mL im 2x/d on d -4 and -3, 0.5 mL 2x/d on d -2 and -1) or 2) no treatment (CON). Estrous behavior was observed for 48 hr; d 0 = expected estrus. Frozen-thawed embryos were transferred (d 7) into the 36 females observed in estrus. Transrectal ultrasonography was used to measure number of CL and size of the largest CL, blood perfusion of luteal tissue, and pregnancy (d 35). Ultrasonography and blood samples were collected on d 7, 14, 21, and 28. Data were analyzed using repeated measures of ANOVA with significance declared at P ≤ 0.05. LSMeans and SEM are presented. On d 21 and 28, cows in the FSH group had decreased (P < 0.05) size of the largest CL compared with CON (d 21 = 1.81±0.309 vs 3.20±0.293 cm 2 and d 28 = 1.88±0.332 vs 2.84±0.322 cm 2 ). Area of blood perfusion was similar between FSH and CON groups (P > 0.05), but on d 21 and 28 it was greater in pregnant cows compared with non-pregnant cows (9.78±2.109 vs 22.43±1.995 and 4.42±2.607 vs 26.38±2.533, P < 0.0001). On d 7, 14, and 21, FSH group had greater concentrations of P4 and number of CL (P ≤ 0.05). Additionally, on d 28, concentrations of P4 and number of CL were greater in FSH-pregnant cows compared to all others (P ≤ 0.05). In conclusion, FSH decreased size of the largest CL but increased number of CL and P4 on most days; it did not affect blood perfusion.